Wjbati - Mashaqi, Amjad; Haj Ali, Thamer (My University, 2018)
Fully automated system to feed the users with the Restaurants in there city and allow them to request a meal that needed from any restaurant in there location. Compatible with Pc & mobile . A web site allow the manager to have a full view on the system with some statistics .